Recognition of facially expressed emotions and visual search strategies in adults with Asperger syndrome - Falkmer, M.; Bjallmark, A.; Larsson, M.; Falkmer, Torbjorn (Elsevier Inc., 2010)
Can the disadvantages persons with Asperger syndrome frequently experience with reading facially expressed emotions be attributed to a different visual perception, affecting their scanning patterns? Visual search strategies, particularly regarding the importance of information from the eye area, and the ability to recognise facially expressed emotions were compared between 24 adults with Asperger syndrome and their matched controls. While wearing a head mounted eye tracker, the participants viewed 12 pairs of photos of faces. The first photo in each pair was cut up into puzzle pieces. Six of the 12 puzzle pieced photos had the eyes bisected. The second photo showed a happy, an angry and a surprised face of the same person as in the puzzle pieced photo. Differences in visual search strategies between the groups were established. Adults with Asperger syndrome had greater difficulties recognizing these basic emotions than controls. The distortion of the eye area affected the ability to identify emotions even more negatively for participants with Asperger syndrome.